Optimization of Singkarak hydropower outflow for renewable micro hydropower development - Rauf, Rosnita; Hadi, Harry Setya; Najif, Hazlif (Jurnal Penelitian Saintek, 2026)
The government’s initiative to enhance energy resilience and independence includes the augmented use of green energy. PLTA Singkarak is a renewable energy facility that harnesses water from Lake Singkarak to operate its turbines, featuring an average tailrace discharge of 30 m³/s. The Singkarak Hydroelectric Power Plant receives its energy from PLN’s Singkarak Substation, utilizing a 5 MVA transformer for distribution to meet its own consumption needs. Consequently, each month, the Singkarak Hydroelectric Power Plant must reduce its total kWh output by its own use, averaging 4,127.8 kW each day. A small-scale Micro Hydro power plant will be developed to utilize the potential water source at the outflow of the Singakrak Hydroelectric Power Plant, serving as the primary supply for the facility, and so decreasing the company’s performance target for its own consumption. A sufficiently big outflow tailrace discharge is likely to be repurposed for a micro-hydropower plant. The initial elevation of the Singkarak Hydroelectric Power Plant tailrace exit is 71 meters above sea level, whereas the end elevation is 67 meters above sea level, as measured by hand. A micro-hydropower plant (PLTMH) can be engineered with a net head of 3.8 m and a flow rate of 10.618 m³/s, yielding a maximum power output of 327.8 kW. The turbine employed is a Kaplan turbine, while the generator utilized is a 3-phase synchronous generator, with both components functioning at 1000 rpm . This PLTMH design can supplant the self-consumption of the Singkarak hydropower plant (PLTA), hence enhancing the system’s energy efficiency.